Utilization of Silica Fume and Sodium Hydroxide in Treated Crumb Rubber for Cement Mortar - Supar, Khairi; Mohammad, Hairuddin; Kaamin, Masiri; Mohammad Azmi, Mohamad Azim; Musa, Mohd Kamaruzaman; Abdul Rahman, Mohammad Ashraf; Ahmad, Hilton; Sugiman, Sugiman (semarak ilmu, 2024)
Cement mortar offers an excellent replacement for materials such as fine aggregate with tire rubber waste in the form of crumbs. It provides excellent environmental and technical benefits to concrete production using recycled materials. As such, it contributes to the sustainable development of the construction industry. This paper mainly emphasizes the strength of untreated and treated crumb rubber from waste tires in cement mortar. Crumb rubber that has been pre-treated with Silica fume (SF) and sodium hydroxide (NaOH) to improve the strength of the mortar mix. This research used a cement-aggregate mix ratio of 1:4 and a water-cement ratio of 1:2. Five different percentages of fine aggregate replacement (0, 3, 6, 9, and 12%) was selected. The compressive strength, density, and water absorption of the mortar were measured at 28 days to find optimum strength. The compressive strength of the cement mortar mixed with treated crumb rubber showed significantly higher values, with an increase of 92% for 12% treated crumb rubber by sodium hydroxide (TN12) compared to untreated crumb rubber. The density value of the mortar cube mixed with treated crumb rubber decreased when the percentage of replacement for treated crumb rubber increased. In the application of roof tiles, lower density values provide an advantage for workability during installation. For water absorption, the treated crumb rubber contributes to a lower percentage of water absorption (acceptable until 6% for SF and 9% for NaOH) compared to the control sample as untreated crumb rubber. Therefore, a mixture of mortar with treated crumb rubber, especially NaOH solution, is better than the untreated crumb rubber specimen.